THE PROBLEM OF THE LEGAL STATUS FORMATION PRISONER’S OF WAR FROM THE END XIX CENTURY TILL THE WORLD WAR I. - KARABIN, О. Yu. (Вісник Черкаського університету. Серія: Історичні науки, 2017)
When in the XIX century the war prisoners started to be under the power and cover of government, which army had them captured, arose a demand of formation of the legal status and determination of generally accepted rules for their holding. The object of the article is to follow this formation process till the beginning of the World War I. Academic novelty is the generality of the earlier published material and the new analysis of the documents that concerning the war prisoners’ status, accepted on international conferences. The important part for the legal status formation and incarceration conditions of war prisoners had the Liber’s Lawbook, that regulated the problem of military imprisonment. These ideas were discussed on the Brussels Conference 1874. There was accepted the proclamation, which regulated among the other problems, issues that were connected with war. But this proclamation was only a recommendation. The next step was Hague Regulations 1899 and 1907. They finalized the Brussels Proclamation and enacted bylaw of laws and ethos of land warfare, in which one of the sections was devoted to this problem, which claimed the legal status of war prisoners’, their providing with food and clothes, right in saving of private property, freedom of conscience, the opportunity to be put on parole, right in correspondence with relatives and also were regulated the issues of using war prisoner work and the payment for it. Consequently on the beginning of the XX century were accepted by the world community the norms of war prisoners’ holding, that fulfilling would be of immense complexity for warring nations during the World War I, when the war prisoners’ quantity was millions of people and the states because of the economic depletion and social tensions could not fulfill all the mentioned in the Proclamation norms of their holding.